2002
DOI: 10.1007/s00216-001-1188-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of selenium in blood serum by inductively coupled plasma atomic emission spectrometry with pneumatic nebulization

Abstract: The possibility of determining selenium in blood serum using inductively coupled plasma emission spectrometry with conventional pneumatic nebulization was studied. A high-resolution spectrometer (SBW=6 pm) with laterally viewed ICP was employed. Analysis with conventional pneumatic nebulization could overcome laborious and demanding digestion, which is necessary for hydride generation. A pressure digestion with nitric acid at 160 degrees C was sufficient to decrease the carbon content in the serum sample to 5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
1
22
0
1
Order By: Relevance
“…Two sets of blood samples were collected before slaughtering from 8 animals per group from the jugular vein, put into two 10-mL vacuum tubes (Venojet VT050SP Terumo, Japan) and subsequently centrifuged (1400 ¥ g ¥ 10 min). Two serum aliquots from each tube were than collected and frozen (-20°C) until analysis for Se (Machát et al, 2002), glucose (Centers for Disease Control, 1976), total protein (Hiller et al, 1948), albumin (Doumas et al, 1971), cholesterol (Allain et al, 1974), alanine transaminase (ALAT) and aspartate transaminase (ASAT) (Henry et al, 1960), bilirubin (Mori, 1978), alkaline phosphatase (ALP) content (Browers and Comb, 1966), and serum glutathione peroxidase activity (GSHPx) (Paglia and Valentine, 1967).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Two sets of blood samples were collected before slaughtering from 8 animals per group from the jugular vein, put into two 10-mL vacuum tubes (Venojet VT050SP Terumo, Japan) and subsequently centrifuged (1400 ¥ g ¥ 10 min). Two serum aliquots from each tube were than collected and frozen (-20°C) until analysis for Se (Machát et al, 2002), glucose (Centers for Disease Control, 1976), total protein (Hiller et al, 1948), albumin (Doumas et al, 1971), cholesterol (Allain et al, 1974), alanine transaminase (ALAT) and aspartate transaminase (ASAT) (Henry et al, 1960), bilirubin (Mori, 1978), alkaline phosphatase (ALP) content (Browers and Comb, 1966), and serum glutathione peroxidase activity (GSHPx) (Paglia and Valentine, 1967).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…For ten years inductively coupled plasma mass spectrometry (ICP-MS) has been regarded as an important technique explored for its potential for selenium analysis [6,7]. Selenium is not as sensitive as other elements owing to its high ionization potential.…”
Section: Introductionmentioning
confidence: 99%
“…However, developments in ICP-MS have shown that it is possible to detect selenium in biological materials and in water or soil with greater sensitivity than by AAS or ICP-AES [8,9]. ICP-MS is a powerful technique for trace elemental analysis [6,7]. But, spectral interferences with limited sensitivity have been improved with ICP-MS coupled with hydride generation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations